The effects of phosphocreatine disodium salts plus blueberry extract supplementation on muscular strength, power, and endurance - John Paul V. Anders; Tyler J. Neltner; Robert W. Smith; Joshua L. Keller; Terry J. Housh; F. Joseph Daugherty; Michael S. Tempesta; Alekha K. Dash; Daniel J. Munt; Richard J. Schmidt; Glen O. Johnson (Taylor & Francis Group, 2021)
Background Numerous studies have demonstrated the efficacy of creatine supplementation for improvements in exercise performance. Few studies, however, have examined the effects of phosphocreatine supplementation on exercise performance. Furthermore, while polyphenols have antioxidant and anti-inflammatory properties, little is known regarding the influence of polyphenol supplementation on muscular strength, power, and endurance. Thus, the purpose of the present study was to compare the effects of 28 days of supplementation with phosphocreatine disodium salts plus blueberry extract (PCDSB), creatine monohydrate (CM), and placebo on measures of muscular strength, power, and endurance. Methods Thirty-three men were randomly assigned to consume either PCDSB, CM, or placebo for 28 days. Peak torque (PT), average power (AP), and percent decline for peak torque (PT%) and average power (AP%) were assessed from a fatigue test consisting of 50 maximal, unilateral, isokinetic leg extensions at 180°·s− 1 before and after the 28 days of supplementation. Individual responses were assessed to examine the proportion of subjects that exceeded a minimal important difference (MID). Results The results demonstrated significant (p < 0.05) improvements in PT for the PCDSB and CM groups from pre- (99.90 ± 22.47 N·m and 99.95 ± 22.50 N·m, respectively) to post-supplementation (119.22 ± 29.87 N·m and 111.97 ± 24.50 N·m, respectively), but no significant (p = 0.112) change for the placebo group. The PCDSB and CM groups also exhibited significant improvements in AP from pre- (140.18 ± 32.08 W and 143.42 ± 33.84 W, respectively) to post-supplementation (170.12 ± 42.68 W and 159.78 ± 31.20 W, respectively), but no significant (p = 0.279) change for the placebo group. A significantly (p < 0.05) greater proportion of subjects in the PCDSB group exceeded the MID for PT compared to the placebo group, but there were no significant (p > 0.05) differences in the proportion of subjects exceeding the MID between the CM and placebo groups or between the CM and PCDSB groups. Conclusions These findings indicated that for the group mean responses, 28 days of supplementation with both PCDSB and CM resulted in increases in PT and AP. The PCDSB, however, may have an advantage over CM when compared to the placebo group for the proportion of individuals that respond favorably to supplementation with meaningful increases in muscular strength.